Developing a Web-Based Information System to Enhance Operations in Hajj and Umrah Travel (Case Study: PT. Mutiara Cinta Imani) - Rosalina, Rosalina; Syahir, Muhammad (ULTIMA InfoSys, 2023)
This research addresses the substantial challenges arising from the prolonged reliance on manual inputting methods, notably paper and Excel, within the operational framework of PT. Mutiara Cinta Imani in the context of Hajj and Umrah travel. The inherent inefficiencies, potential errors, and constraints associated with traditional data management practices have prompted a critical examination of the existing system. Recognizing the imperative for a more contemporary approach, this study focuses on the development and implementation of a Web-Based Information System. The primary goal is to enhance operational efficiency, mitigate errors, and overcome the limitations inherent in manual data management. By conducting a case study on PT. Mutiara Cinta Imani, this research seeks to provide a comprehensive understanding of the challenges faced and propose a technologically advanced solution to optimize data input processes. The envisioned Web-Based Information System aims to revolutionize operations, offering real-time access, scalability, and increased reliability, thereby paving the way for improved practices in the Hajj and Umrah travel domain